The Influence of The Blended Learning Website Based on Creativity in Supporting Students Learning Basic Math - Hermanto, Hermanto; Fauzah, Ana (Insan Akademika Publications, 2025)
This research aims to demonstrate the impact of implementing a Website-based Blended Learning method in enhancing student creativity to support basic mathematics learning. The method used in this study employs the ADDIE development model with 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The resulting learning product underwent validity testing by experts and practicality assessment by students. The products created through student creativity were evaluated using a Paired-sample T-Test to determine whether they were flexible, novel, and elaborative in relation to technological advancements. Research results calculated using SPSS 23 show that the product's practicality score is 0.989, meaning the product is deemed suitable with a